1976
DOI: 10.1093/infdis/133.supplement_2.a140
|View full text |Cite
|
Sign up to set email alerts
|

Small-Particle Aerosols of Antiviral Compounds in Treatment of Type A Influenza Pneumonia in Mice

Abstract: Three chemotherapeutic drugs active against type A influenza virus (amantadine, rimantadine, and ribavirin) were tested as therapeutic agents against established infections with influenza virus in mice. The drugs were administered intraperitoneally or as aerosols either from 6 hr to four days or from three to seven days after infection. Small-particle aerosols were administered continuously 24 hr per day. Continuous dissemination of aerosols was superior to intraperitoneal administration, as evidenced by highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
1

Year Published

1977
1977
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
3
36
1
Order By: Relevance
“…In accord with previous studies of aerosol amantadine therapy in animal models of influenza (7,35,38), aerosol treatments were generally well tolerated. Nasal irritation, rhinorrhea, and disagreeable taste occurred in all subjects receiving treatments with a 2.5-g/100 ml solution concentration, but no adverse effects were observed with the 1.0-g/100 ml concentration.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…In accord with previous studies of aerosol amantadine therapy in animal models of influenza (7,35,38), aerosol treatments were generally well tolerated. Nasal irritation, rhinorrhea, and disagreeable taste occurred in all subjects receiving treatments with a 2.5-g/100 ml solution concentration, but no adverse effects were observed with the 1.0-g/100 ml concentration.…”
Section: Methodssupporting
confidence: 82%
“…Studies of experimentally induced influenza A virus infections of animnals have found greater therapeutic effects when amantadine was administered by the respiratory route as a smallparticle aerosol, as compared with parenteral (38) or oral (7,35) administration. These advantages of topical therapy were demonstrated with dosages of amantadine lower than those given by the other routes.…”
mentioning
confidence: 99%
“…treatment when equivalent doses were compared. (5). Although the effect of aerosol treatment differed significantly from that of the same dosage given i.p.…”
mentioning
confidence: 89%
“…Recently, ribavirin (1-3-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) was found to be effective for the treatment of type A influenza virus infections in mice (1,(3)(4)(5). These experiments indicated that small-particle aerosols (mass median diameter, 1.4 gm) of ribavirin were more effective in reducing mortality, lesions in the lung, and virus concentrations in the lungs than approximately equivalent doses of drug given intraperitoneally (i.p.)…”
mentioning
confidence: 99%
“…This method of drug administration usually results in higher concentrations of drug at the site of infection than systemic administration does, may decrease or ameliorate systemic toxicities seen after systemic administration, and has been more effective than the systemic administration of antiviral agents in murine (31) and ferret (9) animal models of acute influenza virus infection. SPA delivery of antiviral agents has also been effective in the treatment of human respiratory viral diseases (13,14,17,22,24,28).…”
mentioning
confidence: 99%